A financial viability analysis of a RFID system in the microcomputer supply chain - De Castro Filho, Frederico Wergne; Travassos, Lucas X.; Figueiredo, Paulo S. (Revista Gestão da Produção Operações e Sistemas, 2014)
The purpose of this study is to describe a methodology to assess the financial viability of radio frequency identification (RFID) applications and the main contributions of this technology. The impact of RFID technology on supply chain processes was assessed using an Internal Rate of Return analysis. An extensive, six-month discussion and refinement process with the logistics and supply chain managers of the company under study was conducted to validate the procedure and to collect the necessary data. Such technology enables inventory control, tracking of parts/products and customer satisfaction. The viability of using RFID technology for inventory control and product tracking was confirmed. Among the benefits obtained: the reduction of one worker from the inventory team, reduction in the costs for replacing a component and reduction in the costs incurred with defective components were found. This is one of the few attempts to quantify RFDI technology’s contribution. Keywords: Economic Engineering. RFID. Radio Frequency Identification. Financial Viability Analysis. Internal Rate Of Return. Process Automation.